Ariadne's thread: Marxian method in the construction of the Code of Ethics (Temporalis, 2026)
This article aims to recover the foundations of the ethical debate in Brazilian Social Work by taking the reverse path, from the Professional Ethical-Political Project (PEPP) back to its foundations, with the objective of explicating that the political tensions and disputes within the profession are expressions of fundamental social struggles. It argues that the social direction of the PEP, since the hegemony of the Breakaway Intention current, has its most solid and radical foundations in the achievements of the ethical debate developed from the appropriation and use of the Marxian method. To demonstrate this thesis, the article is divided into two parts: the first is dedicated to synthesizing the process of establishing the 1993 Code of Ethics (CE) as a result of the movement of appropriating the Marxian method in the construction of this central document, while the second part analyzes the Marxist elements that drive this project towards the emancipation of a society divided into social classes. The results demonstrate that the appropriation of Marxian theory represents a historic watershed, being fundamental for overcoming the conservative legacy and for shaping the PEP; the 1993 CE, which remains in force, consolidates an ethically grounded ontological conception and introduces freedom as a foundational value. In summary, the appropriation of Marxian theory provided an ontological foundation for Ethics, enabled a radical critique of moralism, and guided the professional project towards class commitment and the horizon of human emancipation.
Keywords: Code of Ethics; Social Work; Marxian method; Professional Ethical-Political Project